On the unique solvability of nonlocal problems with integral conditions for a hybrid system of partial differential equations - Assanova, Anar; Sabalakhova, Aigul (Eurasian Mathematical Journal, 2018)
A nonlocal problem with integral conditions for a hybrid system of partial differential equations is investigated. Based on the results for nonlocal problems for a system of hyperbolic equations, coefficient conditions are established ensuring the existence of classical solutions to a nonlocal problem with integral conditions for a hybrid system of partial differential equations, and algorithms of finding such solutions are suggested.